Evaluation of risk causing factors for the incidence of neck and shoulder pain in adolescents using fuzzy analytic hierarchy process. (24th September 2021) - Padma, T.; Shantharajah, S.P.
The incidence of neck and shoulder pain is recurrent in adolescents, constituting a large socioeconomic challenge and is responsible for substantial personal and social impacts; requiring intensive research to identify potential causes and their precedence in pain occurrence. This study's intent is to explore the prevalence of neck and shoulder pain among adolescents and to examine the risk factors associated with the hazard of the pain. Through knowledge engineering process, risk factors identified are physical-, psychological-, psychosocial-, behavioural-, emotional- and sedentary-related. A fuzzy analytic hierarchy process method is applied to prioritise the risk factors and determines its precedence in pain incidence among the adolescents, categorised based on their ages as early, middle and late adolescence group (between 10-17, 18-21 and 22-24 respectively). The results indicate that the middle adolescence category have a significantly greater chance for pain occurrence. The outcomes will support in decision making and planning for the youth's welfare.